Intimate outsiders : the harem in Ottoman and Orientalist art and travel literature - Roberts, Mary, 1965- (Objects/histories., 2007)
Comparative study of 19th-century representations of Ottoman harems that considers both the tradition of British paintings and writings about harems as well as the perspectives of Ottoman women who commissioned their own harem portraits.